A numerical case study of Arctic stratus in July 1975 - Ohta, Sachio (1982)
P(論文) A numerical simulation was made of the formation of summertime Arctic stratus clouds in July 1975. As stratus is considered to be generated due to cooling of warm moist air advected over polar ice from the area surrounding the Arctic Ocean, monthly averaged radiosonde data measured at Barrow in July 1975 were used as an initial condition. A model is constructed in which a system of equations for a steady-state planetary boundary layer on cloudy days is transformed into a one-dimensional, time-dependent system of equations by introducing the downstream derivative where the time corresponds to travel time moving with a geostrophic wind velocity. We adopt the smoothed eddy diffusion coefficients based on the experimental formula obtained by KONDO under strong stable conditions in the atmospheric surface layer. Upon using the method of the P_3-approximation for calculating the radiative transfer, radiative effects are incorporated into the model including scattering, absorption and emission of radiation by cloud droplets as well as absorption and emission of radiation by gaseous constituents. Clouds are assumed to be composed of pure liquid water droplets with a measured size distribution. The results of calculation are as follows. The cloud appears at a height of about 50m due to lowering of the sea surface temperature. After cloud formation, on account of intense radiative cooling near the top of the cloud, air temperature decreases greatly and a sharp temperature inversion layer is formed in the upper region of the cloud. As the sudden decrease of air temperature enhances condensation of water vapor greatly, the cloud continues developing and gradually rises together with the intense inversion layer. The simulated liquid water content is two times larger than the measured content and the cloud is not separated into two layers, contrary to observation. The disagreement with the measurement seems to be due to insufficient solar radiative heating in our model cloud which is assumed to be composed of pure ...